An Unusual Incarcerated Port Site Hernia due to retained partial gall bladder with stones - A case report. - Hossain, Mohd. Farid; Uddin, Md. Rakib; Emon, Raihanul Islam; Sarkar, Md. Manhbur Rashid (KYAMC Journal, 2013)
A 50 years old lady presented to the Emergency department with what appeared to be a strangulated infraumbilical hernia. She was explored and found to have an unexpected, unusual diagnosis -- incarcerated port site hernia with early features of strangulation. There was fundic part of gall bladder loaded with stones in the center of hernial contents. Gall bladder was surrounded by inflammed pad of omentum. The defect and the mass was approximately 6-8 cm below the umbilical port site incision scar of laparoscopic cholecystectomy, performed 13 years back. Excision of the inflammed hernial contents and Herniorraphy was performed. Patient recovered completely. Complications related to introduction of ports and incomplete removal of gall bladder may present in various ways and sometimes many years after the primary surgery. Methods of reducing the risk of such complications and pathogenesis of hernia in this case are discussed. KYAMC Journal Vol. 3, No.-2, January 2013, Page 309-311 DOI: http://dx.doi.org/10.3329/kyamcj.v3i2.15174